Caffeine Neuroprotective Mechanism Against β-Amyloid Neurotoxicity in SHSY5Y Cell Line: Involvement of Adenosine, Ryanodine, and N-Methyl-D-Aspartate Receptors - Mojtaba Keshavarz; Majid Reza Farrokhi; Atena Amiri (Tabriz University of Medical Sciences, 2017)
Purpose: Some reports have shown neuroprotective effects of caffeine in several neurodegenerative disorders. However, its mechanism of action is not completely clear. Therefore, the aim of this study was to explore the interference of ryanodine, N-methyl-D-aspartate (NMDA) and adenosine modulators with the neuroprotective effects of caffeine against β-amyloid (Aβ) neurotoxicity in the SHSY5Y cells. Methods: The SHSY5Y cells were treated with Aβ23-35 (20µM) and/or caffeine (0.6 and 1mM), or both for 24 hours. Adenosine (20, 40, 60, 80, 100µM), NMDA (20, 50, 70, 90µM), dantrolene (2, 4, 6, 8, 10µM) were also added to the medium and incubated for 24 hours. The cell viability was measured via the MTT (3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyl tetrazolium bromide) method. The data were analyzed using one-way ANOVA followed by Bonferroni test. Results: Caffeine at all the used concentrations (0.6, 0.8, 0.9, 1, and 3mM) significantly protected neuronal cells against Aβ neurotoxicity. Adenosine at the concentrations of 20, 40, 80 and 100μM diminished the neuroprotective effects of caffeine (0.6 and 1mM) against Aβ neurotoxicity. NMDA at the concentrations of 20, 50, 70 and 90μM blocked caffeine (0.6 and 1mM) neuroprotective effects. Dantrolene at the concentration of 2, 4, 6, 8 and 10μM diminished the neuroprotective effects of caffeine (0.6mM) and at the concentrations of 2 and 10μM impede caffeine (1mM) neuroprotection against Aβ neurotoxicity. Conclusion: Caffeine produced neuroprotective effect against Aβ neurotoxicity. Blockade of adenosine and NMDA receptors, as well as the activation of ryanodine receptors, may contribute to the neuroprotective effects of caffeine.